الإيــقاع بين العطاء الفنِّي والاختيار الجمالي نماذج من كتاب الوحشيات لأبي تمام - بن داود, مبروك (University of Eloued جامعة الوادي, 2024)
يسعى هذا المقال إلى الوقوف على واحد من العناصر الأكثر أهمية في الشعر و المتمثل في الإيقاع وكيف اعتمده أبوتمام في عملية انتخاب و اختيار المقطعات الشعرية التي ضمها كتابه الوحشيات؟ حيثُ أنّه بعد تحليــــل المدوَّنة عروضيا وقفنا على نزعةٍ " تمَّاميَّة " تجمع بين الوزن والغرض الشِّعري من جهة ، والصُّورة العروضيَّة لكلِّ بحرٍ وما تفرضه من حركيَّة في الإيقاع من جهة ثانية. Abstract: This article seeks to explore one of the most important elements in poetry, which is rhythm, and how Abu Tammam relied on it in the process of selecting and choosing poetic sections included in his book, "Al-Wehsheyat " . After analyzing the anthology objectively, we discovered a " Temmamian" tendency that combines the purpose of creating poetry and the rhyming on the one hand and the sound structure of each category of poetry "Bahr" , and what it imposes on the movement of the Rhyme on the othe hand
مقال. مجلة علوم اللغة العربية وآدابها. مج16 . ع.01. جامعة الوادي
Keywords: الإيقاع; أبوتمام; الوحشيات; الغرض; العروض; Rhythme; Abu Temmam; Wahsheyat Book; Poetic purpose; Poetic structures